Endocrinology specialty service for inpatients: an unmet growing need - Esther Osher; Naomi Even Zohar; Michal Yacobi-Bach; Dror Cantrell; Merav Serebro; Yael Sofer; Yona Greenman; Karen Tordjman; Naftali Stern (BMC, 2023)
Abstract Background There is recent concern regarding the documented mismatch between demand and supply, vis-à-vis the growing need for trained endocrinologists unmet by parallel rise in the world workforce of endocrinologist. Due to the increasing complexity of disease in inpatients, in recent years we have experienced a growing demand for inpatient endocrine consults. Surprisingly, the need for the endocrinology subspecialty in the overall care of inpatients in the current setting of general hospitals has received little attention. Methods A retrospective analysis of endocrine consult service based on solicited consults carried out during 3 consecutive months. Results During 3 months, there were 767 consults, comprised of 156 diabetes referrals and 611 endocrine/metabolic consult requests. The 611 "non-glucocentric" consult requests were related to 295 inpatients (2.1 ± 2.7 consults/patient). Mean patient age was 58.9 ± .18 years (range 21-92), with some F/M preponderance (58/42%). Requests for endocrine consults were evenly distributed (49.8%, 50.2%) between internal medicine and surgery wards. Case distribution was as follows: thyroid 45.4%, calcium & bone 11.5%, pituitary 12%, adrenal 10% and all others 8.1-0.7%. The mean response time was 4.4 ± 2.7 h. The consults had a discernible effect on the patients' disease management in 60% of the patients. Of these, the consults modified the hospital treatment in 74%, the discharge treatment recommendations in 19% and the diagnosis in 7%. Conclusion At a large medical center, endocrine consults were requested for ~ 3.3% of all admitted inpatients. The endocrine consults modified pre-consult diagnosis or treatment in ~ 60% of the cases. Contrary to its common image as an exclusively outpatient-based subspecialty, endocrinology practiced by specialists and endocrine trainees has a notable role in the daily care of inpatients admitted to a referral general hospital.